Molecular cloning and structural characterization of PPARα gene from turbot (Scophthalmus maximus) and functional exploration of lipid metabolism in response to thermal stress. (14th February 2022) - Zhao, Tingting; Ma, Aijun; Huang, Zhihui; Liu, Zhifeng; Wang, Xinan; Sun, Zhibin; Yang, Jingkun; Li, Yingdi
Abstract: Peroxisome proliferator‐activated receptor alpha ( PPARα ), as a transcription factor, plays an important role in the regulation of lipid metabolism. To better understand the regulatory role of PPARα in lipid metabolism in turbot, we analyzed the sequence structure of PPARα and its stress response to a high temperature. We also investigated the regulation of genes related to lipid metabolism after the knockdown of PPARα . The CDS of PPARα was 1410 bp, encoding 469 amino acids. The relative molecular weight of the protein was 52.64 kDa, and the predicted pI was 5.63. The architecture of the PPARα gene exhibited a ZnF‐C4 domain and a HOLI domain. Phylogenetic analysis indicated that PPARα has been highly conserved during evolution. The qPCR results showed that the mRNA level of PPARα was significantly increased, and the expression of the lipid synthesis genes FASN and SCD was significantly downregulated under high‐temperature stress. PPARα interference and inhibition results showed that the expression levels of FASN and SCD were significantly increased. Our results suggest that high temperatures activate PPARα and inhibit lipid synthesis by downregulating the expression of FASN and SCD in order to reduce lipid deposition and maintain lipid metabolism disorder caused by high‐temperature stress. This is the first report of PPARα in turbot. It will help for studying the evolution of PPARα and provide a reliable reference for studying the regulation mechanism of lipid metabolism in fish under stress.